1994
DOI: 10.1002/j.2334-5837.1994.tb01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Complexity: An Application of Constraint Theory

Abstract: A fundamental intellectual thrust of Systems Engineering thinking is its extensive nature: the ability to integrate across many dimensions and disciplines, and to formulate problems. By contrast, most of our engineering and scientific education has concentrated on intensive thought processes: the concentration on relatively low dimensional submodels and the solution of problems. This paper provides a framework to guide systems engineers in multidimensional thought processes and problem formulation. It is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…So how does an engineer five years beyond a bachelor's degree get trained in a fundamentally different craft? "In attempting to develop graduate level curricula in systems engineering, it has been found that systems engineers cannot be effective until a substantial base of industrial maturity (about five years) is attained, This reinforces the observation that undergraduate engineering curricula do not address the extensive thought processes needed by systems engineers; concentrating, rather, on problem solving techniques" (Friedman, 1994).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…So how does an engineer five years beyond a bachelor's degree get trained in a fundamentally different craft? "In attempting to develop graduate level curricula in systems engineering, it has been found that systems engineers cannot be effective until a substantial base of industrial maturity (about five years) is attained, This reinforces the observation that undergraduate engineering curricula do not address the extensive thought processes needed by systems engineers; concentrating, rather, on problem solving techniques" (Friedman, 1994).…”
mentioning
confidence: 89%
“…At the undergraduate level, most if not all engineers are trained to be domain engineers. It takes about five years of industrial maturity to lead domain engineers into systems engineering (Friedman 1994). Focus must be applied more on the whole, with its synergism and conflict, than on individual domain technologies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If we analyze typical engineering career paths, most engineers spend only 5 to 10 years of their 40+ year nominal careers directly applying the knowledge obtained as part of their undergraduate engineering degree program. McCumber and Sloan [11] citing (Friedman,[12]) observe that most engineers are educated and trained to be "domain engineers." They add that it requires about five years of industrial maturity to evolve engineers into System Engineering.…”
Section: Shifting the Undergraduate Engineering Education Paradigmmentioning
confidence: 99%
“…The ramifications of this view are discussed by Friedman in [Friedman, 1994]. For the nonce, note that the performance of a system is observable at its interface, and that performance is determined by a transfer function which couples some of its parameters (inputs) to other of its parameters (outputs).…”
Section: Introductionmentioning
confidence: 99%